"Learning to listen": boys' gender narratives – implications for theory and practice. Issue 3 (14th March 2016) - Farrell, Francis
Abstract : Purpose: – The purpose of this paper is to critically investigate year 6 and year 9 boys' constructions of masculinity in the light of theories of inclusive masculinity and to consider the implications of the findings for critical masculinities scholarship in educational research. Design/methodology/approach: – Qualitative data was collected through fieldwork in school settings consisting of observations and semi-structured interviews. Data analysis draws upon pro-feminist and post-structuralist theories of the gendered subject. Findings: – The data shows some evidence of inclusive forms of masculinity expressed by the boys' rejection of a "boy code" (Pollack, 1999) and their narratives of caring and emotional experience. However, discourses of dominant masculinity persist and continue to shape the boys' subjectivities. The most striking finding is the capacity of the educational gender work programme reported on in this study to provide boys with the resources to problematise the social construction of masculinity. Research limitations/implications: – The data suggests analysis in binary terms of inclusive or dominant masculinity fails to recognise the fuzzy educational middle ground occupied by the "overlooked ordinary boys" (Brown, 1987; Roberts, 2012) of this study. Practical implications: – Educational gender work programmes which provide boys with the resources to question dominant masculine practices enable boys to exceed the "symbolic order" and trouble dominant gender discourse. Originality/value: – In order to develop nuanced theory and practice researchers need to listen to boys' accounts of their experiences. Analysis of boys gender work in terms of binary adult constructs of masculinity run the risk of perpetuating the essentialism they purport to avoid rather than producing studies which provide an empirically robust foundation for developing an effective practical educational agenda. In a neo-liberal policy context the role of gender equity programmes with the capacity to produce more reflexive masculine subjects requires reassertion within the curriculum.